(untitled) (International Journal of Engineering and Computer Science, 2025)
The article analyzes approaches to the transformation of software solutions based on microservice architecture. The issues of structuring systems are considered, such as the division of functionality, the allocation of separate domain areas, the creation of interfaces, and the management of components and their interaction. The practical aspects of the use of containerization and orchestration technologies, as well as mechanisms for ensuring data reliability and integrity in distributed environments, are highlighted. Examples are given demonstrating the reduction of component interdependence, simplification of update processes, and adaptation of systems to changing conditions. When writing the work, an analytical methodology based on a systematic approach to the collection, study, and synthesis of information was used. Scientific articles published by the author in the public domain, as well as materials that are on the Internet, were used as sources, which made it possible to comprehensively consider the topic. The author focuses on the need for a preliminary analysis of the current system, the development of a clear decomposition strategy, and the use of modern tools for a successful transition to a modular architecture. Recommendations concerning the implementation of container solutions, orchestration systems, continuous integration, and delivery processes are presented. The content is intended for specialists involved in development, architectural design, and infrastructure tasks. These findings demonstrate the potential of the microservice approach as a tool for creating scalable, sustainable applications.